2020
DOI: 10.1177/1947603519900800
|View full text |Cite|
|
Sign up to set email alerts
|

Analysis of Association between Morphometric Parameters of Growth Plate and Bone Growth of Tibia in Mice and Humans

Abstract: Objective The purposes of this study are to evaluate which growth plate parameters are associated with bone growth in mice and to compare the mouse results with those in humans. Design The sagittal sections of the proximal growth plate of the mouse tibia from neonate to young adult stages were subjected to histomorphometric and functional analyses. The radiographic images of tibias of human patients until puberty were analyzed to obtain the tibia length and the proximal growth plate height. It was found that a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…Specialization of vascular morphology within the long bones initiates at postnatal day 6, with metaphyseal capillaries acquiring a column-like structure and diaphyseal capillaries forming a sinusoidal network 28 . Murine long bone growth evolves rapidly until P14, reaching a steady growth phase between P14 and P42 29 , 30 . This is in accordance with the already described rapid decline of the metaphyseal vessels over the first 4 weeks postnatally 7 .…”
Section: Discussionmentioning
confidence: 99%
“…Specialization of vascular morphology within the long bones initiates at postnatal day 6, with metaphyseal capillaries acquiring a column-like structure and diaphyseal capillaries forming a sinusoidal network 28 . Murine long bone growth evolves rapidly until P14, reaching a steady growth phase between P14 and P42 29 , 30 . This is in accordance with the already described rapid decline of the metaphyseal vessels over the first 4 weeks postnatally 7 .…”
Section: Discussionmentioning
confidence: 99%
“…Distinct vascular morphology has been described starting at postnatal day 6 with metaphyseal capillaries (type H vessel) showing a column-like structure and diaphyseal capillaries (type L vessel) forming a sinusoidal network ( 26 ). Murine long bone growth evolves rapidly until P14, reaching a steady growth phase between P14 and P42 ( 27, 28 ). This is in accordance with the already described rapid decline of the Type H vessel over the first 4 weeks postnatally ( 4 ).…”
Section: Discussionmentioning
confidence: 99%
“…The in situ expression of leptin receptor at the GP supported that leptin directly affected the GP. GP thickness was an important histological marker for the longitudinal bone growth ( 34 ). Here, we focused on the GPs and found that the femoral GP was thinner than that of WT mice, and the spinal GP was thicker than that of WT mice.…”
Section: Discussionmentioning
confidence: 99%